Estrategias, estilos de aprendizaje y rendimiento académico en estudiantes ingresantes de Odontología - Ortiz-Fernández, Lita (2014)
The Faculty of Dentistry is committed to the pursuit of quality education, which implies that the learning of the students should be promote by the teachers; they should interact with knowledge through varied activities that meet the individual differences in their relationship with their modes, styles and learning strategies in order to improve their academic performance. This study aims to identify the strategies and learning styles of the incoming students at the Faculty of Dentistry and its relationship to academic performance. Twenty-six students participated voluntarily in the Tutoring Program, this issue had implementation difficulties. Styles and learning strategies were evaluated using questionnaires: Honey-Alonso Learning Styles (CHAEA) and the learning strategies of university students by Gargallo; while academic performance was assessed with the academic record. It was found significant differences between the initial and final extrinsic motivation; also between motivation and academic performance; it was determined that strategies are modified and reflected in their academic performance. It was concluded the incoming student is still in the process of establishing their independence and requires guidance.